Penerapan Teknik Digital Signature Dalam Pengamanan Piagam Penghargaan Menggunakan Algoritma SHA-1 dan RSA - Hanyfa Sari, Nur (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Competition often occurs between individuals to achieve a certain position or position, such as obtaining postgraduate scholarships, applying for jobs, and pursuing important government positions. In addition to research from the aspects of ability and educational background, experience is also one of the factors supporting a person to succeed in achieving the position he wants. To anticipate manipulation or change, digital files can be a solution. Of course, even digital files still need security in order to ensure safety and authenticity (there are no changes to the contents of the file). Therefore we need a solution to this problem, one of the cryptographic techniques that can be used is a digital signature. Choosing a digital signature as a solution is considered very appropriate, because the digital signature is a sign on the data, which can ensure that the data is real (unchanged). So that by applying the digital signature technique to the award certificate, authentication and identification of ownership of the award certificate can be conceptually guaranteed. To protect the maximum validity of a digital file with a digital signature technique, the algorithms that will be used are the SHA-1 and RSA algorithms which are considered sufficient to ensure the security of a digital file.